2019
DOI: 10.1038/s41388-019-1093-y
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of histamine receptor H1 promotes tumor progression and contributes to poor prognosis in hepatocellular carcinoma

Abstract: H1 histamine receptor (H1HR) belongs to the family of rhodopsin-like G-protein-coupled receptors. Recent studies have shown that H1HR expression is increased in several types of cancer. However, its functional roles in tumor progression remain largely unknown, especially in hepatocellular carcinoma (HCC). We found that H1HR is frequently unregulated in HCC, which is significantly associated with both recurrence-free survival and overall survival in HCC patients. Functional experiments revealed that H1HR promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 44 publications
3
41
0
Order By: Relevance
“…6,7,16 Zhao et al reported that upregulated HRH1 promoted tumor progression and contributed to poor prognosis in HCC. 8 Histamine and histamine receptors have been identified as critical molecules during inflammation and carcinogenesis, which might be potential molecular target for cancer therapeutics. 6,17 Abnormal expression of HRH3 has been reported in different types of cancer, including HCC, cholangiocarcinoma, melanoma, pancreatic, and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,16 Zhao et al reported that upregulated HRH1 promoted tumor progression and contributed to poor prognosis in HCC. 8 Histamine and histamine receptors have been identified as critical molecules during inflammation and carcinogenesis, which might be potential molecular target for cancer therapeutics. 6,17 Abnormal expression of HRH3 has been reported in different types of cancer, including HCC, cholangiocarcinoma, melanoma, pancreatic, and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…5 Abnormal expression levels of histamine receptors have been reported in different types of human cancers. [5][6][7][8][9] Zhao et al reported that upregulation of HRH1 promoted tumor progression and contributed to poor prognosis in hepatocellular carcinoma. 8 Tanaka demonstrated that both HRH2 antagonist cimetidine and HRH3 antagonist clobenpropit attenuated inflammation-associated colorectal carcinogenesis in male ICR mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCs are able to express and secrete MMP2 and MMP9 to liberate VEGF and fibroblast growth factor (bFGF) from the ECM and thus to stimulate angiogenesis 52 . Also, it has been found that the interaction between MCs‐secreted histamine and its receptor 1, H1 (H1HR), can drive cell‐cycle progression, MMP2 production, and suppression of apoptosis 53 . In addition to tumor enhancing characteristics, studies have suggested that MCs also have immunomodulatory effects on cancer cells 54 .…”
Section: Cell Types In the Tmementioning
confidence: 99%
“…Although the mechanism of action of miR-940 is still unclear, current studies have shown that miR-940 not only interregulates with some other non-coding RNAs ( Figure 4 ), but it also downregulates the expression of 29 genes ( Table 1 ). By regulating the functions of many downstream genes, miR-940 can affect cell proliferation, 21 migration, 23 invasion, 15 apoptosis, 11 cell cycle, 35 EMT, 40 osteogenic differentiation, 12 and other biological processes ( Figure 2 ).
Figure 2 miR-940 affects the biological process of cells through target genes miR-940 affects cell proliferation, migration, invasion, apoptosis, EMT, cell cycle, and osteogenic differentiation by regulating target genes.
…”
Section: Introductionmentioning
confidence: 99%